2017
DOI: 10.1186/s12879-017-2316-x
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic HIV Env C5/gp41 vaccine candidate Vacc-C5 induces specific T cell regulation in a phase I/II clinical study

Abstract: BackgroundLevels of non-neutralising antibodies (AB) to the C5 domain of HIV Env gp120 are inversely related to progression of HIV infection. In this phase I/II clinical study we investigated safety of Vacc-C5, a peptide-based therapeutic vaccine candidate corresponding to C5/gp41732–744 as well as the effects on pre-existing AB levels to C5/gp41732–744, immune activation and T cell responses including exploratory assessments of Vacc-C5-induced T cell regulation. Our hypothesis was that exposure of the C5 pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Brekke and colleagues combined HIV Vacc-C5, containing residues 489–511 from the HIV-1 virus C5 domain, with GM-CSF adjuvant as a peptide-based therapeutic vaccine against HIV [ 196 ]. In this Phase 1/2 clinical study, Vacc-C5 adjuvanted with GM-CSF was intramuscularly administrated to 36 participants and provided evidence for the GM-CSF-adjuvanted vaccine to be safe and well-tolerated in all patients and induce the stronger T cell immune response compared to vaccine alone (NCT01627678) [ 73 ]. A Phase 1 clinical trial in progress is assessing a vaccine containing dendritic cells loaded with S-protein from SARS-CoV-2 alongside GM-CSF as an adjuvant intramuscularly injected in 175 non-infected participants to evaluate its safety and anti-SARS-CoV-2 immunity (NCT04386252) [ 74 ].…”
Section: Immunostimulatory Complexesmentioning
confidence: 99%
“…Brekke and colleagues combined HIV Vacc-C5, containing residues 489–511 from the HIV-1 virus C5 domain, with GM-CSF adjuvant as a peptide-based therapeutic vaccine against HIV [ 196 ]. In this Phase 1/2 clinical study, Vacc-C5 adjuvanted with GM-CSF was intramuscularly administrated to 36 participants and provided evidence for the GM-CSF-adjuvanted vaccine to be safe and well-tolerated in all patients and induce the stronger T cell immune response compared to vaccine alone (NCT01627678) [ 73 ]. A Phase 1 clinical trial in progress is assessing a vaccine containing dendritic cells loaded with S-protein from SARS-CoV-2 alongside GM-CSF as an adjuvant intramuscularly injected in 175 non-infected participants to evaluate its safety and anti-SARS-CoV-2 immunity (NCT04386252) [ 74 ].…”
Section: Immunostimulatory Complexesmentioning
confidence: 99%
“…Currently, there is no vaccine for HIV-1, with many trials rendering unsatisfying results ( Tebas et al, 2012 ; Pollard et al, 2014 ; Ensoli et al, 2015 ; Dinges et al, 2016 ; Macatangay et al, 2016 ; Jacobson et al, 2016a , b ; Brekke et al, 2017 ), which is often attributed to the extensive genetic diversity that is exhibited by HIV-1. Recent work investigates the use of mRNA-based vaccines that incorporate multiple HIV subtypes, in order to cover a larger genetic diversity ( Aidsmap, 2021 ).…”
Section: Pharmaceutical and Non-pharmaceutical Interventionsmentioning
confidence: 99%
“…GM-CSF has also been used as an adjuvant to combat viral infections such as HIV and COVID-19, based on its ability to enhance DC maturation, and their ability to present viral antigens [ 138 ]. Previous HIV trials employing GM-CSF as an adjuvant reported inconsistent results with various positive or negative outcomes including no effect compared to controls.…”
Section: Gm-csf In Clinical Trials and Immunotherapymentioning
confidence: 99%
“…Previous HIV trials employing GM-CSF as an adjuvant reported inconsistent results with various positive or negative outcomes including no effect compared to controls. A recent HIV trial (NCT01627678) [ 139 ], used Vacc-C5 (a peptide vaccine) with GM-CSF as an adjuvant to ameliorate the vaccine’s immunogenicity and help increase T cell levels [ 138 ] reported only marginal changes. A trial in progress is assessing a vaccine composed of DC loaded with antigens from COVID-19 alongside GM-CSF as an adjuvant in non-infected participants to evaluate if it enhances anti-COVID-19 immunity (NCT04386252) [ 140 ].…”
Section: Gm-csf In Clinical Trials and Immunotherapymentioning
confidence: 99%